The compassionate leadership profile: A case study in the saving and loan cooperative leadership of Bhina Raharja - Syahrul Alim; Novita Paradhita Wulandari; Titin Florentina Purwasetiawatik (Communications in Humanities and Social Sciences, 2021)
The leadership style has a big impact on how well an organization achieves its objectives and it serves as the driving force behind the organizations decision-making. An ideal organization employs an effective and efficient leadership style. This study aims to observe the leadership behaviors at Bhina Raharja Savings and Loan Cooperative in Central Java. In-depth interviews were conducted to four informants: the top leader, human resource, branch leader, and treasurer. The findings revealed that the leadership present was unique and distinct. Every process was based on trust and fraternity, and the leadership was generally pleasant. The organization's mission was not limited to monetary gains. Furthermore, the courageous attitude of giving in and valuing brotherhood became a distinguishing feature. This leadership style is known as compassionate leadership, and it has been used in the Bhina Raharja Cooperative by highlighting the elements of trust, kindness, and humanity.